Resubmission of purchase fire protection coating quantities for steel member surface - BUCG-ABC Joint Venture (BUCG-ABC JV) (2023)
This record consists of general correspondence regarding resubmission of purchase fire protection coating quantities for steel member surface for BRACU new campus project.